The role of citizen science in addressing plastic pollution: Challenges and opportunities. Issue 128 (February 2022) - Nelms, Sarah E.; Easman, Emily; Anderson, Nichola; Berg, Madeleine; Coates, Sue; Crosby, Abigail; Eisfeld-Pierantonio, Sonja; Eyles, Lauran; Flux, Tony; Gilford, Emily; Giner, Claire; Hamlet, Jasper; et al.
Abstract: Globally, the number of citizen science clean-up projects, such as beach cleans, is increasing in an effort to reduce the amount of plastic pollution in the environment. Such activities offer the opportunity to gather insightful data on plastic abundance, distribution and composition. This information is key for informing effective management strategies aimed at reducing input but little work has been conducted to examine the challenges faced by existing citizen science projects, or the potential opportunities for maximising their impact. Here, we present the results of a questionnaire survey and follow-up workshop to explore the opinions of representatives from 20 organisations that deal with the issue of plastic pollution in the environment. Our results show that, of the organisations that conduct clean-up activities in the United Kingdom (UK), the majority collect data on plastic pollution to some extent. To ensure these data are scientifically meaningful and the necessary levels of public engagement are maintained, participants felt that survey protocols should be standardised across organisations and data submission should be as simple and easy as possible. The participants considered communication, inclusivity and volunteer diversity to be key for enhancing citizen engagement and improving data quality. Many organisations were unclear about how the information they hold can be most effectively used to help inform policies relating to managing plastic pollution. Moving forwards, there is a clear desire from clean-up organisations to collaborate with other sectors, such as commercial, policy, waste and recycling, education and technology stakeholders, as well as other non-governmental organisations and scientific researchers, to enhance the value and impact of citizen science in tackling the issue of plastic pollution. Highlights: The challenges and opportunities of using citizen science to address plastic pollution were explored. Most clean-up organisations collect data on plastic pollution but protocols should be simple and standardised to ensure utility. Communication, inclusivity and diversity are key for enhancing citizen engagement. Citizen science offers great value for informing evidence-based policy aimed at reducing plastic pollution.